Los criterios epistemológicos en la investigación económica - Orozco Livia, Victor (2013)
Capitalism has changed with globalization, together with the progress of science, technology and philosophy. The changes that have generated economic paradigms crisis. Monetarist theory, many government official, has been challenged by the economic facts, showing deficiencies that come from their epistemological pillars. If monetarist theory asserts its epistemological criteria that research is observation of phenomena, such description picture prevents entities or events thought to reach the internal causes that lead to the behavior of the objects of study. This is why the 2008 financial crisis still not resolved by the end of 2012. Monetarist economic measures only affect the image or appearance of the crisis, but not in content. Scientific research requires epistemological criteria that allow the research process to go beyond the appearances of the object of study and get to the internal properties caused the crisis. Only by knowing the inner nature of the crisis can reverse it.